Analisis Kemampuan Membaca Permulaan Peserta Didik Berdasarkan Hasil Early Greade Reading Assessment - Ningruum, Sekar Tyas Ayu; Profithasari, Nindy; Khairani, Fadhilah; Astuti, Nelly (Didaktika Dwija Indria, 2025)
The problem in this study was related to the difficulties in beginning reading, which became an obstacle for students in participating in learning activities in grade 1 of elementary school. The purpose of this study was to analyze the beginning reading ability of grade 1of elementary school. The type of research used in this study was qualitative research presented in descriptive form. This study involved students, teachers, and parents. The data were obtained through interviews, tests, and documentation. Data collection used the purposive sampling technique, which was data collection based on certain considerations. The results of this study showed that the beginning reading ability of grade 1 students, as measured by the five aspects of EGRA, included 7 students categorized as very good readers, 8 students categorized as good readers, 7 students categorized as sufficient readers, and 5 students categorized as poor readers. The average beginning reading ability of grade 1 of elementary schoolwas 74.25, which fell into the good category. The beginning reading ability of the students was influenced by internal and external factors.